2022
DOI: 10.1111/1759-7714.14542
|View full text |Cite
|
Sign up to set email alerts
|

Multiple primary pulmonary meningioma: A case report and literature review

Abstract: Lung cancer has become a leading cause of cancer‐related deaths. With the conventional use of low‐dose spiral computed tomography (CT) in physical examinations, an increasing number of small pulmonary nodules are screened. However, primary pulmonary meningiomas (PPMs) are rarely reported. Here, we report the case of a 64‐year‐old woman who had a CT scan during physical examination, which revealed three ground‐glass‐like opacity pulmonary nodules in both lungs. The patient underwent video‐assisted thoracoscopic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 10 publications
0
20
0
Order By: Relevance
“…Lung is the most common metastatic site with occurrence up to several years after the excision of the primary tumor. Ectopic meningiomas account for 2% of meningiomas and PPM is rare, whilst mPPM is exceptional, with only six patients (including our report) being reported to the best of our knowledge so far (11)(12)(13)(14)(15)(16)(17). PPM tends to occur in middle-aged females.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Lung is the most common metastatic site with occurrence up to several years after the excision of the primary tumor. Ectopic meningiomas account for 2% of meningiomas and PPM is rare, whilst mPPM is exceptional, with only six patients (including our report) being reported to the best of our knowledge so far (11)(12)(13)(14)(15)(16)(17). PPM tends to occur in middle-aged females.…”
Section: Discussionmentioning
confidence: 56%
“…Pubmed research revealed 177 articles from 1968 to 2022, of which seven were considered eligible after ltering our initial selection (11)(12)(13)(14)(15)(16)(17). Three out of seven articles were authored by the same researchers and concerned the same patient (surgery, ten-and twenty-years follow-up).…”
Section: Review Of Published Casesmentioning
confidence: 99%
“…This manifestation is rare, and very few similar cases have been reported [ 7–9 , 33 ]. In two of these cases, different nodules were sampled, and histology confirmed the diagnosis of multiple PPM [ 7 , 8 ]. For other cases, the diagnosis was based on the histology of the largest lesion, and small nodules were on active surveillance [ 9 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 8 ] PPM is more likely to occur in middle-aged and older women. [ 9 ] Although most patients are asymptomatic, some may have symptoms such as chest pain, coughing and hemoptysis. [ 10 ]…”
Section: Discussionmentioning
confidence: 99%
“…[8] PPM is more likely to occur in middle-aged and older women. [9] Although most patients are asymptomatic, some may have symptoms such as chest pain, coughing and hemoptysis. [10] In the most cases, PPM is usually found incidentally and often appears as solitary solid pulmonary nodules on chest CT scan.…”
Section: Discussionmentioning
confidence: 99%